Study on dynamic phenomena in voltage-mode controlled single-phase half-bridge inverters - Fei-Hu Hsieh; Hen-Kung Wang; Po-Lun Chang; Hsuan-Chiang Wu (2012 International Conference on Machine Learning and Cybernetics, 2012)
This paper proposes related research of the nonlinear dynamic behaviors in voltage-mode controlled single-phase half-bridge inverters. The system exhibits nonlinear dynamic behaviors from period-l operation through period-doubling bifurcations to chaos state using the proportional gain changeable, variable DC input voltage and load resistance. First, a mathematical model of single-phase half-bridge inverter is derived. Then, SIMULINK software tools are used to construct models, simulate results and verify the nonlinear dynamic behaviors in this inverter.